Characterization and preparation of Polyvinyl Alcohol (PVA) as inhibitor in formation of hydrates - Najihah, Jamil; Hazlina, Husin; Ahmad Waseem, Alfida; Zachary, Aman; Zulkafli, Hassan (Unique Research Publishers, 2018)
The thermal properties of PVA with different degree of hydrolysis (DH) was studied by preparation of aqueous polymer solution, followed by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FTIR). The DSC result showed the typical partially crystalline materials, showing some phases of separation are characterized by a glass transition (Tg = 25-26 °C) related to the amorphous part of the material, followed by two endothermic peaks related to the melting point (Tm = 185-225) of the crystallites. Due to the same material (PVA) used, the main composition temperatures are close to each other (for peak I between 320 K and 350 K, and for peak II between 429 K and 430 K). Finally, FTIR confirmed that between the three materials P 100, P 87 and P 85, there were distinctness in the band absorbed between fully hydrolysed PVA, P 100 and partially hydrolysed PVA, P 85 and P 87.